Hyperechogenicity of lenticulostriate vessels: A poor prognosis or a normal variant? A seven year retrospective study - Candice Fabre; Barthélémy Tosello; Estelle Pipon; Catherine Gire; Kathia Chaumoitre (Elsevier, 2018)
Background: Lenticulostriate vasculopathy (LSV) is a hyperechogenicity of the lenticulostriate branches of the basal ganglia and/or thalamus' middle cerebral arteries and is frequently seen in neonatology. Our study primarily describes the perinatal data and long-term follow-up of newborns with lenticulostriate vessel hyperechoic degeneration. Secondly, it describes the cerebral imaging data as a function of perinatal factors and neurodevelopmental follow-up of these newborns. Methods: This retrospective study assesses the outcome of newborns with LSV hyperechogenicity on cerebral ultrasound (two grades). These children were born between January 2008 and September 2015 and were treated in a large level III neonatal intensive care unit. Thirty-four term-equivalent age children underwent MRIs using a standardized protocol of T2, T1 3D, diffusion and spectro-MRI sequences. The MRIs retrospectively measured the white matter and basal ganglia apparent diffusion coefficients (ADC). Results: Fifty-eight neonates, ranging from 25 to 42 weeks gestational age (GA), were diagnosed with LSV. There was a significantly increased high-grade LSV when accompanied by fetal heart rate abnormalities (p = 0.03) and the neonate's need for respiratory support at birth (P = 0.002). The mean ADC score was substantially superior in the high-grade versus the low-grade LSVs (p = 0.023). There were no noteworthy outcome differences between a high and low grade LSV. The mean ADC for basal ganglions was appreciably higher in children with a severe prognoses (death or developmental disorder) as compared to children with no abnormalities (p < 0.01). Conclusion: From the results of our study, it appears that a low-grade LSV could be considered as a normal variant. There are no unifying diagnostic criteria for LSV on cerebral ultrasound. With a cerebral MRI, the use of ADC values of basal ganglia may well underscore the importance of such data in predicting long-term outcomes. Keywords: lenticulostriate vasculopathy, magnetic resonance imaging, newborn, outcome